1996
DOI: 10.1002/jbmr.5650110213
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemically administered PDGF-BB on the rodent skeleton

Abstract: Platelet-derived growth factor (PDGF), an osteoblast mitogen, has been demonstrated to accelerate fracture healing and periodontal bone repair when applied locally in vivo. To explore whether PDGF could stimulate bone formation in intact bone, we administered it systemically to rats rendered acutely estrogen-deficient. Because PDGF may stimulate bone resorption in vitro, PDGF was administered with and without an antiresorptive agent (alendronate). All treatments were given by intravenous injection 3 times a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Our findings of increased expression of Csf1 and Tnfsf11, an increased number of TRAP + osteoclasts at the bone surface, and elevated serum CTX-1 levels in PGK-PDGFB-treated mice are entirely consistent with a PDGF-BB-induced increase in bone resorption. Accordingly, inasmuch as the serum PTH was normal in the PGK-PDGFB-treated group, we interpret this finding to be consistent with previous reports on the innate ability of PDGF-BB to stimulate bone resorption (11). Such an increase in bone resorption is indicative of an increase in bone remodeling, which could increase bone quality and improve the mechanical performance of bone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of increased expression of Csf1 and Tnfsf11, an increased number of TRAP + osteoclasts at the bone surface, and elevated serum CTX-1 levels in PGK-PDGFB-treated mice are entirely consistent with a PDGF-BB-induced increase in bone resorption. Accordingly, inasmuch as the serum PTH was normal in the PGK-PDGFB-treated group, we interpret this finding to be consistent with previous reports on the innate ability of PDGF-BB to stimulate bone resorption (11). Such an increase in bone resorption is indicative of an increase in bone remodeling, which could increase bone quality and improve the mechanical performance of bone.…”
Section: Discussionsupporting
confidence: 91%
“…We use the term PDGFB to refer the gene that encodes the human platelet-derived growth factor (PDGF) B chain, and the term PDGF-BB to refer the homodimeric protein. PDGF-BB is a major growth factor found in bone matrix (10) and has also been shown to increase bone formation after intravenous administration (11). In addition, there have been considerable successful applications of PDGF-BB-based therapies on various types of maladies, including tendon, periodontal ligament, and bone fracture repairs (12,13).…”
mentioning
confidence: 99%
“…19 There is clear clinical advantage for ease of use for a single local dose of rhPDGF-BB applied directly to a fracture to accelerate healing that we report, in contrast to a systemic dose administered multiple times as described by Mitlak et al 19 Moreover, Nash et al found rhPDGF-BB combined with a collagen sponge improved fracture repair in a rabbit model. 18 In summary, to the best of our knowledge, this is the first study to report rhPDGF-BB enhanced fracture healing in an osteoporotic animal model that was also geriatric.…”
Section: Discussionmentioning
confidence: 57%
“…19 Additionally, rhPDGF-BB enhanced bone formation in periodontal defects in dogs. 20 In human patients with advanced periodontal lesions, rhPDGF-BB combined with allograft bone matrix stimulated alveolar bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…PDGF-BB also increases the number of rat osteoblasts in vivo. 51 In human and murine cells, osteoblast survival is thought be stimulated by PDGF-BB through the phosphorylation of Akt. 52 Therefore, a decrease in osteoclast development and activity may also result from imatinib and nilotinib therapy.…”
Section: Src Kinase Inhibition: Myelosuppressionmentioning
confidence: 99%